Androgenetic alopecia (New capillary protocol in androgenic alopecia) (Research, Society and Development, 2020)
Objective: To elaborate and validate, internally, a protocol, directed to the investigation regarding possible cases of alopecia of androgenic pattern in a test group of university students enrolled in the private education network of Fortaleza. Methodology: Seven judges with expertise in the field of dermatology and / or trichology and who have at least two years as a dermatologist and in work activities during the data collection period were selected for validation of the protocol, obeying the minimum pre-established profile of five points, through own criteria adapted from Fehring (1994). To validate the items in the questionnaire, the Likert scale (1932) was used. The item's relevance criterion was considered to be at least 80% agreement between the experts. Results: The average length of time for the judges was 10.42 years. Any characteristic that identifies the judges was removed from the survey results. In total, 20 items were analyzed for clarity, conciseness, language suitability and applicability, with grades from one to four and a space for suggestions. Items 3, 6, 7, 8, 10 and 12 were accepted with a suggestion given by the judges. No items have been omitted from the previous version. Conclusion: Internal validation revealed high levels of approval, obtaining grades 3 and 4 in 95% of the answers, requiring minor adjustments. The degree of agreement of the items of at least 80% between the judges was obeyed. Therefore, this instrument can be applied to undergraduate students with the intention of identifying individuals who have capillary disorders related to androgenic alopecia.